Ahl Al-Kitab and the Laws of Marriage (Implementation of Interpretation Method) - Birahmat, Budi; Dedi, Syarial (AJIS: Academic Journal of Islamic Studies, 2023)
The issuance of SEMA (Supreme Court Circular Letter) No. 2 of 2023, revived the discussion about the meaning of ahl al-kitab in surah al-Maidah verse 5. Al-Qur'an as a holy book is responsible for explaining the terms used so that people do not misunderstand them, according to one of its functions, namely, al-baiyyinah (explainer). One of them is the term ahl al-kitab. This study is very important because it relates to the issue of marriage. This paper aims to understand the meaning of ahl al-kitab in the Qur’an by using the interpretation method that has been passed down by scholars. This was done to be guided and avoid mistakes. This study is in the form of library research (literature) with a method (content analysis) in the form of reduction, verification, and inference steps. This paper concludes that Ahl al-kitab are Jews and Christians descended from the Children of Israel who still believe, and they are the ones who are allowed to marry. Even so, reality teaches that a new marriage will be lasting and peaceful, if there is conformity in the views of life between husband and wife, especially in matters of religion.